Seagrass Ecosystem Carbon Stock In The Small Islands: Case Study In Spermonde Island, South Sulawesi, Indonesia - Agustin Rustam; Nasir Sudirman; Restu Nur Afi Ati; Hadiwijaya Lesmana Salim; Yusmiana Puspitaningsih Rahayu (Jurnal Segara, 2017)
Small islands are particularly rich with coral reefs and seagrass ecosystems and coastal plants. Seagrass is one of the coastal ecosystems of blue carbon, which is capable of storing utilize and store CO2 in the form of organic carbon in biomass and sediment. The purpose of this study to get the carbon stock of seagrass and its role in climate change. The survey method with sampling purposive sampling representing all research sites and analyzed the amount of carbon contained in biomass and sediment. The result showed that there were eight species of seagrass found, and the highest carbon stock  on the type Enhalus acoroides at  Kapoposang island was 1.64 MgC / ha. The average value of the total biomass of carbon stock in the island's largest seagrass Bauluang island  was 1.89 ± 0.92 Mg C / ha with the largest at the ground below 77% of total carbon biomass. Carbon stock in sediments of seagrass ecosystems average of 531.87 ± 74.08 Mg C / ha up to a depth of 50 cm. The role of seagrass in Spermonde archipelago waters in climate change in both the biomass and sediment for MgC 533.25 MgC/ ha is equivalent to the use of CO2 for 1955.26 MgCO2e / ha.